My Arabic Wiki: an innovative model of teaching and learning Arabic writing skills via the Wiki - Md Ghalib, Mohd. Feham; Zainuddin, Nurkhamimi (2011)
My Arabic Wiki: An Innovative Model of Teaching and Learning Arabic Writing Skills Via The Wiki (006-UIAM). Category:Information and Communication Technology(ICT) Research Exhibition of i-INOVA organised by USIM and MoHE.